Media Pembelajaran Pengenalan Lambang Bilangan Pada Anak Usia 4-6 Tahun: Kajian Literatur - Fauziyyah, Adinda Nur; Rusijono, Rusijono; Susarno, Lamijan Hadi (Jurnal Ilmiah Mandala Education (JIME), 2023)
This study aims to determine the learning media for the introduction of number symbols for Early Childhood Education. The data in this study were obtained through a literature study research method. The researcher collects and analyzes all the data in the study from various existing sources to obtain information relevant to the problem to be solved through a systematic technique using the keywords symbol number and early childhood education. The data or information comes from books, theses, theses, journals and research articles from official websites that have been indexed and accredited. Early Childhood Education basically has to pay attention to aspects of development in children, especially cognitive development to recognize number symbols. The introduction of number symbols emphasizes the understanding of number symbols that must be understood by children. Children aged 4-6 years are in the pre-operational stage, the stage where children begin to recognize symbols or symbols, so teachers need interesting learning media as a tool to introduce number plates to children so that children can easily understand the material and learning will become more meaningful. The results of the study show a variety of learning media developed to help introduce number symbols to children aged 4-6 years